Shape–color associations in an unrestricted color choice paradigm - Zelazny, Aurore; Liu, Xun; Sørensen, Thomas Alrik (Frontiers in Psychology, 2023)
Since Kandinsky's claim for fundamental shape–color associations, several studies have revealed that those tendencies were not generalizable to the entire population and that different associations were more prevalent. Past studies, however, lacked a methodology that allowed participants to freely report their shape–color preferences. Here, we report data from 7,517 Danish individuals, using a free choice full color wheel for five different geometrical shapes. We find significant shape–hue associations for circle-red/yellow, triangle-green/yellow, square-blue, and pentagon/hexagon-magenta. The significant shape–hue associations are also more saturated than non-significant ones for the circle, triangle, and square. At the conceptual level, basic shapes, which show stronger associations, are linked to primary colors, and non-basic shapes to secondary colors. Shape-color associations seem indeed to follow the Berlin-Kay stages of entry into languages. This pattern had previously been described for graphemes and weekday–color associations. The methodology employed in our study can be repeated in different cultural contexts in the future. We also provide another instance of color associations for ordinal concepts that follow the stages of entry into languages.